Strength and power determinants of grinding performance in America's Cup sailors - Pearson, S. N.; Hume, P. A.; Cronin, J. B.; Slyfield, D. (The Journal of Strength and Conditioning Research, 2009)
The purpose grinding is a physically demanding component of America's Cup sailing that is important to overall team performance, but little research is available on the determinants of grinding performance. We examined the relationship between various measures of muscular performance and the performance of upper-body grinding. Eleven elite male America's Cup sailors (33.9 ± 5.5 yr, 97.8 ± 12.5 kg, 186.0 ± 7.1 cm) who performed grinding as part of their on-board role with extensive strength training experience participated in this study. Muscular performance testing examined the force, velocity, and power capabilities of the upper-body musculature, with upper-body push (bench press) and pull (bench pull) movements performed across loads of 10-100% of 1 repetition maximum (1RM). Functional grinding performance was examined for both forward and backward grinding and at 2 different resistances (moderate = 48 N·m, heavy = 68 N·m) using a land-based ergometer. Bench press 1RM and maximum force capability were the measures demonstrating the strongest correlation with forward grinding performance (r = 0.88-0.99 and 0.87-0.99, respectively), with the relationship increasing with grinding load. For backward grinding, there was a very strong relationship with bench pull maximum power (r = 0.85-0.98) in addition to 1RM (r = 0.90-0.95) and maximum force (r = 0.87-0.95). It appears that although maximal strength is a crucial muscular performance characteristic for grinding performance in all conditions, for backward grinding, there is the additional need to focus on the development of speed strength/power to maximize performance gains. This information was used by the Emirates Team New Zealand physical conditioner to develop a conditioning intervention to help improve grinding performance.